g-C3N4 hydrogel composite aniline hydrogel, preparation method and application

Through the photocatalytic coupling system of g-C3N4 hydrogel composite aniline hydrogel and permonosulfate, the problems of low efficiency and slow reaction rate in the prior art are solved, and the efficient degradation of methylhydrazine is achieved. and the method has a wide range of pH application, and the catalyst is easy to reuse, avoiding metal dissolution and secondary contamination.

CN115772275BActive Publication Date: 2024-12-20SICHUAN RONGSHI ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211526244.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-30
Publication Date
2024-12-20
Estimated Expiration
2042-11-30

AI Technical Summary

Technical Problem

Existing chemical treatment methods are used for methylhydrazine wastewater treatment with low efficiency and slow reaction rate, especially advanced oxidation technology based on permonosulfate requires a large amount of energy under UV activation, and existing catalysts are degrading methylhydrazine. There is a problem of insufficient efficiency.

Method used

Using g-C3N4 hydrogel composite aniline hydrogel as catalyst support, the composite hydrogel with porous structure and graphite phase carbon nitride dispersion is prepared, and photocatalytic coupling is combined with persulfate to improve catalytic activity and degradation efficiency. .

Benefits of technology

The degradation efficiency of methylhydrazine was significantly improved, and the degradation efficiency increased from 20% to 97% within 60 minutes, the primary kinetic constant increased from 0.00394 min-1 to 0.05621 min-1, and showed better under ultraviolet light. Catalytic effect, and this method has a wide range of application to pH, and the catalyst is easy to reuse, avoiding metal dissolution and secondary contamination.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115772275B_ABST
    Figure CN115772275B_ABST
Patent Text Reader

Abstract

The invention discloses a g-C3N4 hydrogel composite aniline hydrogel, a preparation method and an application, including preparing g-C3N4 nanosheets by heating melamine in stages; mixing and heating N,N'-methylenebisacrylamide, alkali solution, initiator and aniline, and absorbing water to obtain a hydrogel by a coagulant; mixing and placing concentrated sulfuric acid-aniline solution, g-C3N4 nanosheets, phytic acid and hydrogel, and then adding ammonium persulfate, sealing at low temperature, and obtaining a g-C3N4 hydrogel composite hydrogel. The composite hydrogel of the present invention has an obvious porous structure, a tight network structure, a complete porous closure, a large pore size, and a high transmittance; and graphite phase carbon nitride is evenly dispersed, providing more binding sites for photocatalysis. The composite hydrogel of the present invention can be used as a catalyst carrier to act on peroxymonosulfate to synergistically photocatalyze the degradation of methylhydrazine in sewage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of hydrogels, and in particular to a gC 3 N 4 The invention relates to a preparation method of a hydrogel composite aniline hydrogel and its application in the field of methylhydrazine catalytic degradation. Background Art

[0002] Methylhydrazine is a high-energy fuel with excellent performance and is widely used in rocket launches. However, it is highly toxic and easy to decompose, and it is very easy to cause water pollution during transportation and cleaning. At present, physical treatment, biological treatment and chemical treatment are widely used in the treatment of methylhydrazine wastewater, but due to factors such as cost, reaction rate, and degradation mechanism, the actual methylhydrazine degradation effect using physical and biological methods is far from the expected one. Chemical methods (including catalytic oxidation, acidic oxidation potential water oxidation, photocatalytic oxidation, etc.) are more effective. Among them, the advanced oxidation technology based on permonosulfate (PMS) produces sulfate free radicals (•SO4 - ) are strong oxidizing active species, which can directly degrade mineralized organic pollutants or improve their biodegradability. At the same time, they have strong oxidizing ability and high treatment efficiency, so they have good application prospects. However, the reaction rate of PMS itself is slow, and it is often combined with exogenous activation methods, including ultraviolet light activation, thermal activation, etc., which requires a lot of energy. Among them, ultraviolet light activation using sunlight as energy has the advantages of being green, environmentally friendly and sustainable. The development of corresponding photocatalyst materials under ultraviolet light is expected to further increase the decomposition rate of PMS, and thus improve its degradation efficiency of methylhydrazine.

[0003] Using hydrogel as a catalyst carrier for pollutant degradation has become a new development trend. As an adsorption material, hydrogel is widely used in heavy metal adsorption, removal of organic pollutants, etc. It has good adsorption capacity and low price. It is characterized by a three-dimensional network structure, rich in hydrophilic groups, and can introduce specific functional groups such as amino, hydroxyl, carboxyl, amide, etc., which builds a good platform for the loading of catalysts. Using hydrogel as a catalyst carrier can improve the catalytic activity of the catalyst and improve the degradation efficiency of pollutants on the one hand; on the other hand, it can also improve the recovery rate of the catalyst while avoiding negative impacts on the environment.

[0004] Cellulose hydrogel is a hydrogel composed of cellulose molecules or cellulose nanoparticles (including cellulose nanofibers, cellulose nanocrystals, bacterial cellulose, etc.). There are a large number of hydroxyl groups on the surface of cellulose, which show strong hydrophilicity, so they can maintain good compatibility with the hydrophilic hydrogel matrix. Since the active hydroxyl groups are suitable for various chemical reactions, the interaction between the filler and the matrix can be further enhanced by surface modification of cellulose, thereby improving its dispersibility.

[0005] As a polymer semiconductor material, graphene carbon nitride has a bandgap of about 2.7 eV and can absorb blue-violet light with a wavelength less than 475 nm in the solar spectrum. The good position of the valence band and conduction band makes gC 3 N 4 It has good optical properties. In addition, its excellent chemical stability and low cost make it a good solar catalyst, and it has good application prospects in energy and environmental fields such as new energy photocatalysis and photocatalytic treatment of pollutants. Nanostructured gC 3 N 4 While improving the reaction activity under light conditions, it can provide more active sites for photocatalysis, and related research fields have received great attention. Summary of the invention

[0006] In order to solve the above-mentioned defects in the prior art, the purpose of the present invention is to provide a gC for hydrazine wastewater treatment. 3 N 4 Preparation method of hydrogel composite aniline hydrogel, aiming to construct gC 3 N 4 The hydrogel composite aniline hydrogel activated PMS synergistic photocatalytic coupling system solves the technical problems of low efficiency and slow reaction rate of existing chemical treatment methods. The composite hydrogel of the invention has a significant porous structure, a tight network structure, complete porous closure, a large pore size, and high transmittance; the graphite phase carbon nitride is evenly dispersed, providing more binding sites for photocatalysis.

[0007] The present invention is achieved through the following technical solutions.

[0008] In one aspect, the present invention provides a gC 3 N 4 The preparation method of hydrogel composite aniline hydrogel comprises:

[0009] a. Melamine is heated in stages to obtain gC 3 N 4 Powder and gC 3 N 4 Nanosheets;

[0010] b. Stir and mix N,N'-methylenebisacrylamide, alkali solution, initiator and aniline in a mass ratio of (5-10):1:(1-2):(1.5-2.5) in a water bath to obtain solution A;

[0011] Heat solution A in a water bath until solidified, place the solidified product in deionized water to absorb water, obtain a hydrogel, and refrigerate for later use;

[0012] c. Add concentrated sulfuric acid-aniline solution, gC 3 N 4 , the mass ratio of phytic acid and hydrogel is (2.0-4.0): (0.5-1.0): (0.5-1.0): 1, stirred and mixed, allowed to stand, and then (0.03-0.05) ammonium persulfate was added to the mixed solution to obtain solution B;

[0013] Take the mixed solution B and seal it at low temperature to obtain gC 3 N 4 Hydrogel composite aniline hydrogel.

[0014] Preferably, in step a, melamine is heated to 450-600°C and maintained for 2-6 h at a heating rate of 1-10°C / min to obtain a yellow gC 3 N 4 powder;

[0015] G C 3 N 4 The powder is heated to 450~600℃ and maintained for 2~6 h to obtain a light yellow gC 3 N 4 Nanosheets.

[0016] Preferably, the alkali solution is sodium hydroxide, potassium hydroxide or ammonia water.

[0017] Preferably, the initiator is potassium persulfate, sodium persulfate or ammonium persulfate.

[0018] Preferably, the concentrated sulfuric acid-aniline solution is prepared according to a volume ratio of concentrated sulfuric acid to aniline of (20-30):1.

[0019] Preferably, in step b, solution A is poured into a rubber-tipped dropper, heated in a water bath at 50 to 70 °C for 3 to 6 h until completely solidified, the solidified material is taken out and absorbed in deionized water for 20 to 28 h, and the deionized water is replaced every 5 to 8 h; the hydrogel is refrigerated at -12 to -20 °C for 10 to 15 h, and thawed for 2 to 6 h before being chopped.

[0020] Preferably, in step c, the mixed solution is allowed to stand for 2 to 4 hours before adding ammonium persulfate.

[0021] Preferably, the hydrogel and the mixed solution are sealed in an environment of 0-5 °C for 36-60 h to obtain gC 3 N 4 Hydrogel composite aniline hydrogel.

[0022] The gC prepared by the present invention 3 N 4The porous structure of the hydrogel composite aniline hydrogel comes from steps b and c. In step b, repeated freezing and thawing of the hydrogel produces a porous structure, and in step c, aniline and graphite phase carbon nitride are added to determine the shape of the porous structure.

[0023] The graphite phase carbon nitride is evenly dispersed, providing more binding sites for photocatalysis. It comes from step c, adding powdered graphite phase carbon nitride nanosheets and aniline to make the graphite phase carbon nitride enter the already formed hydrogel through powder diffusion. Compared with adding graphite phase carbon nitride to the liquid during the preparation of hydrogel, this method makes the powder distribution more even.

[0024] Another aspect of the present invention provides gC prepared by the method 3 N 4 Hydrogel composite aniline hydrogel.

[0025] In another aspect, the present invention provides a method for degrading methylhydrazine using the composite hydrogel, comprising:

[0026] Add 6-9 g / L gC in the wastewater containing methylhydrazine according to the mass ratio 3 N 4 The hydrogel is composited with aniline hydrogel and 0.7-1.0 g / L potassium permonosulfate or potassium hydrogen permonosulfate, and a degradation reaction is carried out at a pH of 6-8 under irradiation of ultraviolet light.

[0027] The present invention adopts the above technical solution, which has the following beneficial effects:

[0028] 1. The present invention has a better degradation effect on methylhydrazine. Compared with graphite phase carbon nitride powder, gC 3 N 4 The degradation efficiency of methylhydrazine by hydrogel composite aniline hydrogel increased from 20% to 97% within 60 min, and the first-order kinetic constant (k) increased from 0.00394 min -1 Increased to 0.05621 min -1, The photocatalytic effect is significantly better than that of graphite carbon nitride powder. During the degradation process, the porous structure of the hydrogel provides a pathway for the transfer of methylhydrazine molecules. Compared with graphite carbon nitride powder, methylhydrazine can be more easily transferred and aggregated in the catalyst. At the same time, the polymer semiconductor polyaniline promotes the transfer of holes and electrons generated by graphite carbon nitride under ultraviolet light to the surface of the material, thereby showing a better degradation effect.

[0029] 2. The present invention synthesizes gC by graphite phase carbon nitride and polyaniline 3 N 4The hydrogel composite aniline hydrogel utilizes the porous structure of the hydrogel and the light-responsive properties of carbon nitride to achieve high-efficiency catalytic activity and stability, achieving the effect of efficiently activating persulfate under light conditions to degrade pollutants.

[0030] 3. The method for degrading methylhydrazine of the present invention has a wide pH applicable range, and the non-metallic catalyst is easy to reuse, has no metal dissolution, and has no secondary pollution, which is more conducive to practical application. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The drawings described herein are used to provide a further understanding of the present invention, constitute a part of the present application, and do not constitute an improper limitation of the present invention. In the drawings:

[0032] Figure 1 This is a schematic diagram of the production process of the composite hydrogel of the present invention;

[0033] Figure 2 This is a physical diagram of the composite hydrogel production process of the present invention;

[0034] Figure 3 gC 3 N 4 SEM image of hydrogel composite aniline hydrogel;

[0035] Figure 4 gC 3 N 4 FT-IR spectrum of hydrogel composite aniline hydrogel;

[0036] Figure 5 gC 3 N 4 XRD pattern of hydrogel composite aniline hydrogel;

[0037] Figure 6 (a) and (b) are graphite phase carbon nitride powder and gC 3 N 4 Comparison of the degradation effects of hydrogel composite aniline hydrogel on methylhydrazine. DETAILED DESCRIPTION

[0038] The present invention will be described in detail below in conjunction with the accompanying drawings and specific embodiments. The exemplary embodiments and descriptions of the present invention are used to explain the present invention but are not intended to limit the present invention.

[0039] The gC provided in the embodiment of the present invention 3 N 4 The preparation method of the hydrogel composite aniline hydrogel comprises the following steps:

[0040] Step a, using melamine as raw material, preparing gC 3 N 4 Nanosheets:

[0041] (a1) Melamine was placed in an alumina crucible, covered, and placed in a KSL-1200X muffle furnace. The crucible was heated to 450-600°C at a heating rate of 1-10°C / min and maintained for 2-6 h to obtain a yellow powder of gC. 3 N 4 powder;

[0042] (a2) Take the above gC 3 N 4 The powder was placed in an alumina crucible, covered, and placed in a muffle furnace at a heating rate of 1-10°C / min, heated to 450-600°C and maintained for 2-6 h to obtain a light yellow solid, gC 3 N 4 Nanosheets.

[0043] Step b, preparing hydrogel:

[0044] (b1) 5 to 10 parts by weight of N,N'-methylenebisacrylamide, 1 part by weight of alkali solution (sodium hydroxide, potassium hydroxide or aqueous ammonia), 1 to 2 parts by weight of initiator (potassium persulfate, sodium persulfate or ammonium persulfate) and 1.5 to 2.5 parts by weight of aniline are mixed and stirred in a water bath for 10 to 20 minutes to obtain a solution A;

[0045] (b2) Take a disposable 5 mL plastic dropper, keep the head of the dropper, cut off 4 cm from the bottom, pour solution A into the dropper, seal it with a string, and heat it in a 50-70 ℃ water bath for 3-6 h until it is completely solidified;

[0046] (b3) Cut open the rubber dropper along the sealing line with scissors, take out the solidified material and absorb it in deionized water for 20 to 28 hours. Change the deionized water every 5 to 8 hours and record the amount of water absorbed by the hydrogel each time.

[0047] (b4) Refrigerate the above hydrogel at -12 to -20 °C for 10 to 15 h. Thaw it for 2 to 6 h, chop it into pieces with a paper cutter, and refrigerate it for later use.

[0048] Step c, preparation of gC 3 N 4 Hydrogel composite aniline hydrogel, such as Figure 1 , Figure 2 As shown:

[0049] (c1) Concentrated sulfuric acid-aniline solution, gC 3 N 4 The mass ratio of nanosheets, phytic acid and hydrogel is (2.0-4.0): (0.5-1.0): (0.5-1.0): 1. After fully stirring and mixing, the mixed solution is placed at room temperature for 2-4 h;

[0050] The concentrated sulfuric acid-aniline solution is prepared according to a volume ratio of concentrated sulfuric acid to aniline of (20-30):1;

[0051] (c2) Add (0.03-0.05) parts of ammonium persulfate to the mixed solution, and stir the test solution with a glass rod to mix well to obtain solution B;

[0052] (c3) The composite hydrogel and the mixed solution were sealed at 0-5 °C for 36-60 h to obtain a dark green gC 3 N 4 Hydrogel composite aniline hydrogel.

[0053] like Figure 3 As shown, through SEM scanning electron microscopy analysis, gC 3 N 4 The hydrogel composite aniline hydrogel presents a porous network structure.

[0054] As shown in Figure 4, through FTIR analysis, it can be obtained that gC 3 N 4 Spectrum of hydrogel composite aniline hydrogel at 2830 cm -1 There is an absorption peak at 2 ) vibration stretching peak; at 1580 cm -1 The stretching vibration peak of the imino group (NH) appears at 781 cm -1 The non-planar vibration of the imino group at 1630 cm -1 The absorption peak at 3390 cm-1 is the symmetrical stretching vibration peak of carboxylate (COO-). -1 The broad peak of hydroxyl (-OH) at 1360 cm -1 The characteristic peak at indicates the presence of carboxyl (C-OH) groups in the composite hydrogel.

[0055] like Figure 5 As shown, through X-ray diffraction analysis, the three diffraction peaks are 15.3°, 20.7°, and 25.2°, which are attributed to the (011), (020), and (200) crystal planes of polyaniline.

[0056] The gC prepared by the above method 3 N 4 The hydrogel composite aniline aniline hydrogel is used in treating wastewater containing methylhydrazine, comprising the following steps:

[0057] Add 6-9 g / L gC in the wastewater containing methylhydrazine according to the mass ratio 3 N4 The hydrogel was composited with aniline hydrogel and 0.7-1.0 g / L potassium permonosulfate, and the degradation reaction was carried out at pH 6-8 under ultraviolet light irradiation.

[0058] The following is a specific example of the gC prepared by the present invention. 3 N 4 The hydrogel composite aniline hydrogel material is further described.

[0059] Example 1

[0060] C 3 N 4 Preparation of hydrogel composite aniline hydrogel:

[0061] a. Preparation of gC 3 N 4 Nanosheets:

[0062] (a1) Melamine was heated to 500°C at a heating rate of 5°C / min and maintained for 3 h to obtain a yellow powder of gC 3 N 4 powder;

[0063] (a2) Take the above gC 3 N 4 The powder was heated to 450 °C in a muffle furnace at a heating rate of 5 °C / min and maintained for 6 h to obtain a light yellow solid of gC 3 N 4 Nanosheets.

[0064] Step b, preparing hydrogel:

[0065] (b1) 8 parts by weight of N,N'-methylenebisacrylamide, 1 part by weight of sodium hydroxide, 1 part by weight of initiator potassium persulfate, and 2 parts by weight of aniline were mixed and stirred in a water bath for 15 min to obtain a solution A;

[0066] (b2) Take a 5 mL plastic pipette, keep the head of the pipette, cut off 4 cm from the bottom, pour solution A into the pipette, seal it with a string, and heat it in a 65℃ water bath for 5 h until it is completely solidified;

[0067] (b3) Take out the coagulated material and absorb water in deionized water for 25 h. Change the deionized water every 6 h and record the amount of water absorbed by the hydrogel each time.

[0068] (b4) Refrigerate the above hydrogel at -15 °C for 12 h, thaw for 4 h, and then cut it into pieces with a paper cutter.

[0069] Step c, preparation of gC 3 N 4 Hydrogel composite aniline hydrogel:

[0070] (c1) Concentrated sulfuric acid-aniline solution, gC 3 N 4 The mass ratio of nanosheets, phytic acid and hydrogel was 2.0: 0.8: 0.5: 1. After being fully stirred and mixed, the mixed solution was placed at room temperature for 3 h.

[0071] The concentrated sulfuric acid-aniline solution was prepared according to a volume ratio of concentrated sulfuric acid to aniline of 25:1;

[0072] (c2) adding 0.03 parts of ammonium persulfate to the mixed solution and mixing well to obtain solution B;

[0073] (c3) The composite hydrogel and the mixed solution were sealed at 5 °C for 36 h to obtain a dark green gC 3 N 4 Hydrogel composite aniline hydrogel.

[0074] Example 2

[0075] C 3 N 4 Preparation of hydrogel composite aniline hydrogel:

[0076] a. Preparation of gC 3 N 4 Nanosheets:

[0077] (a1) Melamine was heated to 450°C at a heating rate of 8°C / min and maintained for 4 h to obtain a yellow powder of gC 3 N 4 powder;

[0078] (a2) Take the above gC 3 N 4 The powder was heated to 500 °C in a muffle furnace at a heating rate of 8 °C / min and maintained for 4 h to obtain a light yellow solid of gC 3 N 4 Nanosheets.

[0079] Step b, preparing hydrogel:

[0080] (b1) 5 parts by weight of N,N'-methylenebisacrylamide, 1 part by weight of potassium hydroxide, 1.5 parts by weight of initiator sodium persulfate, and 1.5 parts by weight of aniline were mixed and stirred in a water bath for 20 min to obtain a solution A;

[0081] (b2) Take a 5 mL plastic pipette, keep the head of the pipette, cut off 4 cm from the bottom, pour solution A into the pipette, seal it with a string, and heat it in a 50°C water bath for 6 h until it is completely solidified;

[0082] (b3) Take out the coagulated material and absorb water in deionized water for 20 h. Change the deionized water every 8 h and record the amount of water absorbed by the hydrogel each time.

[0083] (b4) Refrigerate the hydrogel at -18 °C for 14 h, thaw for 2 h, and then chop it with a paper cutter.

[0084] Step c, preparation of gC 3 N 4 Hydrogel composite aniline hydrogel:

[0085] (c1) Concentrated sulfuric acid-aniline solution, gC 3 N 4 The mass ratio of nanosheets, phytic acid and hydrogel was 3.0:0.5:0.7:1. After being fully stirred and mixed, the mixed solution was placed at room temperature for 2 h.

[0086] The concentrated sulfuric acid-aniline solution was prepared according to a volume ratio of concentrated sulfuric acid to aniline of 30:1;

[0087] (c2) adding 0.04 parts of ammonium persulfate to the mixed solution and mixing well to obtain solution B;

[0088] (c3) The composite hydrogel and the mixed solution were sealed at 2 °C for 40 h to obtain a dark green gC 3 N 4 Hydrogel composite aniline hydrogel.

[0089] Example 3

[0090] C 3 N 4 Preparation of hydrogel composite aniline hydrogel:

[0091] a. Preparation of gC 3 N 4 Nanosheets:

[0092] (a1) Melamine was heated to 550°C at a heating rate of 10°C / min and maintained for 2 h to obtain a yellow powder of gC 3 N 4 powder;

[0093] (a2) Take the above gC 3 N 4 The powder was heated to 600 °C in a muffle furnace at a heating rate of 10 °C / min and maintained for 2 h to obtain a light yellow solid of gC 3 N 4 Nanosheets.

[0094] Step b, preparing hydrogel:

[0095] (b1) 10 parts by weight of N,N'-methylenebisacrylamide, 1 part by weight of aqueous ammonia, 2 parts by weight of initiator ammonium persulfate, and 2.5 parts by weight of aniline were mixed and stirred in a water bath for 10 min to obtain a solution A;

[0096] (b2) Take a 5 mL plastic pipette, keep the head of the pipette, cut off 4 cm from the bottom, pour solution A into the pipette, seal it with a string, and heat it in a 55°C water bath for 4 h until it is completely solidified;

[0097] (b3) Take out the coagulated material and absorb water in deionized water for 28 h, change the deionized water every 5 h, and record the amount of water absorbed by the hydrogel each time;

[0098] (b4) Refrigerate the above hydrogel at -20 °C for 10 h, thaw for 6 h, and then cut it into pieces with a paper cutter.

[0099] Step c, preparation of gC 3 N 4 Hydrogel composite aniline hydrogel:

[0100] (c1) Concentrated sulfuric acid-aniline solution, gC 3 N 4 The mass ratio of nanosheets, phytic acid and hydrogel was 3.5:1.0:1.0:1. After being fully stirred and mixed, the mixed solution was placed at room temperature for 4 h;

[0101] The concentrated sulfuric acid-aniline solution was prepared according to a volume ratio of concentrated sulfuric acid to aniline of 20:1;

[0102] (c2) adding 0.05 parts of ammonium persulfate to the mixed solution and mixing well to obtain solution B;

[0103] (c3) The composite hydrogel and the mixed solution were sealed at 4 °C for 50 h to obtain a dark green gC 3 N 4 Hydrogel composite aniline hydrogel.

[0104] Example 4

[0105] C 3 N 4 Preparation of hydrogel composite aniline hydrogel:

[0106] a. Preparation of gC 3 N 4 Nanosheets:

[0107] (a1) Melamine was heated to 600°C at a heating rate of 1°C / min and maintained for 6 h to obtain a yellow powder of gC 3 N 4 powder;

[0108] (a2) Take the above gC 3 N 4 The powder was heated to 550 °C in a muffle furnace at a heating rate of 1 °C / min and maintained for 5 h to obtain a light yellow solid of gC 3 N 4 Nanosheets.

[0109] Step b, preparing hydrogel:

[0110] (b1) 6 parts by weight of N,N'-methylenebisacrylamide, 1 part by weight of sodium hydroxide, 1.6 parts by weight of initiator sodium persulfate, and 2.2 parts by weight of aniline were mixed and stirred in a water bath for 18 minutes to obtain a solution A;

[0111] (b2) Take a 5 mL plastic pipette, keep the head of the pipette, cut off 4 cm from the bottom, pour solution A into the pipette, seal it with a string, and heat it in a 70 °C water bath for 3 h until it is completely solidified;

[0112] (b3) Take out the coagulated material and absorb water in deionized water for 22 h. Change the deionized water every 7 h and record the amount of water absorbed by the hydrogel each time.

[0113] (b4) Refrigerate the above hydrogel at -12 °C for 15 h, thaw for 3 h, and then cut it into pieces with a paper cutter.

[0114] Step c, preparation of gC 3 N 4 Hydrogel composite aniline hydrogel:

[0115] (c1) Concentrated sulfuric acid-aniline solution, gC 3 N 4 The mass ratio of nanosheets, phytic acid and hydrogel was 4.0: 0.5: 0.6: 1. After being fully stirred and mixed, the mixed solution was placed at room temperature for 3 h.

[0116] The concentrated sulfuric acid-aniline solution was prepared according to a volume ratio of concentrated sulfuric acid to aniline of 20:1;

[0117] (c2) adding 0.035 parts of ammonium persulfate to the mixed solution and mixing well to obtain solution B;

[0118] (c3) The composite hydrogel and the mixed solution were sealed at 0 °C for 60 h to obtain a dark green gC 3 N 4 Hydrogel composite aniline hydrogel.

[0119] The gC prepared by the above method 3 N 4Hydrogel composite aniline aniline hydrogel.

[0120] The following is the gC prepared in Example 3 N 4 The performance of hydrogel composite aniline aniline hydrogel material was tested.

[0121] Product composition: 5 mL 99% acrylic acid, 10 mL 0.05 mol / L sodium hydroxide solution, 0.5 mL 0.063 g / mL ammonium persulfate solution, 1 mL 0.042 g / mL N,N'-methylenebisacrylamide solution, 2.72 mL 98% concentrated sulfuric acid, 0.582 g gC 3 N 4 , 0.114 mL aniline and 0.413 g phytic acid.

[0122] Structure: As Figure 3 As shown, through SEM scanning electron microscopy analysis, gC 3 N 4 The hydrogel composite aniline hydrogel presents a porous network structure.

[0123] As shown in Figure 4, through FTIR analysis, it can be obtained that gC 3 N 4 Spectrum of hydrogel composite aniline hydrogel at 2830 cm -1 There is an absorption peak at 2 ) vibration stretching peak; at 1580 cm -1 The stretching vibration peak of the imino group (NH) appears at 781 cm -1 The non-planar vibration of the imino group at 1630 cm -1 The absorption peak at 3390 cm-1 is the symmetrical stretching vibration peak of carboxylate (COO-). -1 The broad peak of hydroxyl (-OH) at 1360 cm -1 The characteristic peak at indicates the presence of carboxyl (C-OH) groups in the composite hydrogel.

[0124] like Figure 5 As shown, through X-ray diffraction analysis, the three diffraction peaks are 15.3°, 20.7°, and 25.2°, which are attributed to the (011), (020), and (200) crystal planes of polyaniline.

[0125] G C 3 N 4 The application of hydrogel composite aniline hydrogel in treating wastewater containing methylhydrazine was studied. 3 N 4The degradation ability of the hydrogel composite aniline hydrogel activated PMS photocatalytic coupling system on methylhydrazine is shown below. 3 N 4 Hydrogel composite aniline hydrogel material for the degradation of methylhydrazine in wastewater.

[0126] 1. Different catalyst dosage

[0127] To study different gC 3 N 4 Degradation efficiency of methylhydrazine under the addition amount of hydrogel composite aniline hydrogel. In two beakers containing 20 mg / L methylhydrazine solution, 6.0 g / L, 7.0 g / L, 8.0 g / L and 9.0 g / L of gC were added respectively. 3 N 4 The hydrogel was composited with aniline hydrogel and the above operation was performed. The absorbance of the solution was measured after sampling at the specified time point, and the methylhydrazine concentration (C f ) and initial concentration (C 0 ) (methylhydrazine concentration at the time of adding peroxymonosulfate) represents the corresponding gC 3 N 4 Degradation efficiency of methylhydrazine in solution at different addition amounts of hydrogel composite aniline hydrogel.

[0128] 100 mL of an aqueous solution of methylhydrazine with a concentration of 20 mg / L was added to the reactor, and 6.0, 7.0, 8.0, and 9.0 g / L of gC obtained in Example 1 were added to the reactor. 3 N 4 The hydrogel composite aniline hydrogel and 1.0 g / L potassium persulfate or potassium hydrogen persulfate were subjected to magnetic stirring in a reactor, and reacted under the condition of pH=8 under the irradiation of ultraviolet light, and the experimental results were tested after 60 minutes.

[0129] The removal rates of methylhydrazine under different catalyst addition conditions are shown in Table 1.

[0130] Table 1: Degradation effect of different catalyst dosages on methylhydrazine

[0131]

[0132] When the amount of potassium permonosulfate or potassium hydrogen permonosulfate added was 1.0 g / L, the methylhydrazine concentration was 20 mg / L, and pH = 8, the degradation efficiency of methylhydrazine increased with the increase in the amount of catalyst added. However, after the amount of catalyst added exceeded 9 g / L, the degradation efficiency of methylhydrazine began to decrease. Therefore, it can be inferred that the optimal catalyst dosage for degrading methylhydrazine simulated waste liquid in this experiment is 9 g / L.

[0133] The results showed that gC 3 N 4 The hydrogel composite aniline hydrogel has the function of catalyzing the degradation of methylhydrazine by peroxymonosulfate, and with the increase of gC 3 N 4 The degradation efficiency of methylhydrazine increases with the increase of the hydrogel composite aniline hydrogel. This is because during the degradation process, the porous structure of the hydrogel provides a path for the transfer of methylhydrazine molecules. As the content of the composite hydrogel increases, the methylhydrazine molecules can be more easily aggregated in the composite hydrogel, thus showing better degradation.

[0134] 2. Different persulfate dosage

[0135] C 3 N 4 The degradation efficiency of methylhydrazine in hydrogel composite aniline hydrogel under different PMS amount environments. 3 N 4 Degradation efficiency of methylhydrazine in hydrogel composite aniline hydrogel under different PMS amount environments. 100 mL of methylhydrazine aqueous solution with a concentration of 20 mg / L was added to the reactor. At the same time, 0.7, 0.8, 0.9, 1.0 g / L of potassium permonosulfate or potassium hydrogen permonosulfate and 9 g / L of gC obtained in Example 1 were added to the reactor. 3 N 4 The hydrogel composite aniline hydrogel was subjected to magnetic stirring in a reactor, and reacted under ultraviolet light at room temperature and pH=8. The experimental results were tested after 60 minutes.

[0136] The removal rates of methylhydrazine under different addition amounts of potassium permonosulfate or potassium hydrogen permonosulfate are shown in Table 2.

[0137] Table 2: Degradation effect of different PMS dosages on methylhydrazine

[0138]

[0139] After sampling at the specified time point, the absorbance value of the solution was measured, and the corresponding methylhydrazine concentration was calculated. Finally, the methylhydrazine concentration corresponding to the degradation time of 60 minutes after the addition of peroxymonosulfate was selected (C f ) and initial concentration (C 0 ) (methylhydrazine concentration at the time of adding peroxymonosulfate) represents the corresponding gC 3 N 4 Degradation efficiency of methylhydrazine in solution at different addition amounts of hydrogel composite aniline hydrogel.

[0140] When the added catalyst dosage was 9 g / L, the methylhydrazine concentration was 20 mg / L, and pH = 8, with the increase of potassium permonosulfate or potassium hydrogen permonosulfate added, the degradation efficiency of methylhydrazine also increased. However, after the addition of potassium permonosulfate or potassium hydrogen permonosulfate exceeded 1.0 g / L, the degradation efficiency of methylhydrazine began to decrease. Therefore, it can be inferred that the optimal dosage of potassium permonosulfate or potassium hydrogen permonosulfate for degrading methylhydrazine simulated waste liquid in this experiment is 1.0 g / L.

[0141] C 3 N 4 The hydrogel composite aniline hydrogel has the function of catalyzing the degradation of methylhydrazine by peroxymonosulfate, and within a certain range, as the concentration of peroxymonosulfate in the solution increases, the degradation efficiency of methylhydrazine increases. This is because as the amount of peroxymonosulfate added increases, sulfate free radicals (SO 4 • - ) increased, thereby greatly improving the degradation efficiency of methylhydrazine.

[0142] 3. Different initial pH

[0143] To study gC 3 N 4 The degradation efficiency of methylhydrazine in hydrogel composite aniline hydrogel under different pH environments was studied. Four experimental groups were set up. 3 N 4 Before the hydrogel was composited with aniline hydrogel, sodium hydroxide (NaOH) solution was used to change the pH value of the methylhydrazine solution so that the pH in the beakers of the four experimental groups was 6, 7, 8, and 10, respectively, and gC was controlled. 3 N 4 The dosage of the hydrogel composite aniline hydrogel was 9.0 g / L, and the dosage of potassium persulfate or potassium hydrogen persulfate was 1.0 g / L. After sampling at the specified time point, the absorbance value of the solution was measured, and the corresponding methylhydrazine concentration was calculated. Finally, the methylhydrazine concentration corresponding to the degradation time of 60 minutes after the addition of persulfate was selected (C f ) and initial concentration (C 0 ) (methylhydrazine concentration at the time of adding peroxymonosulfate) represents the corresponding gC 3 N 4 Degradation efficiency of methylhydrazine in solution at different addition amounts of hydrogel composite aniline hydrogel.

[0144] 100 mL of an aqueous solution with a methylhydrazine concentration of 20 mg / L was added to the reactor, and the initial pH was changed to 6, 7, 8, and 10. At the same time, 1.0 g / L of potassium permonosulfate or potassium hydrogen permonosulfate and 8.39 g / L of the ink-phase carbon nitride / nanocellulose composite hydrogel obtained in Example 1 were added to the reactor, magnetic stirring was performed in the reactor, and the reaction was carried out at room temperature under ultraviolet light. The experimental results were tested after 60 minutes.

[0145] The removal rates of methylhydrazine under different pH conditions are shown in Table 3.

[0146] Table 3: Degradation effect of different initial pH on methylhydrazine

[0147]

[0148] The results show that the degradation of hydrogel is pH responsive. The degradation efficiency is the highest under neutral conditions at pH = 7, and the degradation rate reaches 98% in 60 minutes. The degradation efficiency is the slowest under weak acidic conditions at pH = 6, and the degradation efficiency is only 95.2% in 60 minutes. The degradation rate is 98.8% in 60 minutes under pH = 8 conditions, and 80.2% in 60 minutes under alkaline conditions at pH = 10. The results show that gC 3 N 4 The hydrogel composite aniline hydrogel not only catalyzes the degradation of methylhydrazine by peroxymonosulfate, but also has pH influence, and the catalytic degradation efficiency is highest under neutral conditions.

[0149] When the added catalyst dosage was 9 g / L, the dosage of potassium permonosulfate or potassium hydrogen permonosulfate was 1.0 g / L, and the methylhydrazine concentration was 20 mg / L, the degradation efficiency of methylhydrazine increased with the increase of pH. However, after the initial pH exceeded 8, the degradation efficiency of methylhydrazine began to decrease. Therefore, it can be inferred that the optimal initial pH for degrading methylhydrazine simulated waste liquid in this experiment is 8.

[0150] As shown in Figure 6 (a) and (b), compared with graphite phase carbon nitride powder, the present invention has a better degradation effect on methyl hydrazine. 3 N 4 The degradation efficiency of methylhydrazine by hydrogel composite aniline hydrogel increased from 20% to 99% within 60 min, and the first-order kinetic constant (k) increased from 0.00394 min -1 Increased to 0.05621 min -1,The photocatalytic effect is significantly better than that of graphite carbon nitride powder. During the degradation process, the porous structure of the hydrogel provides a pathway for the transfer of methylhydrazine molecules. Compared with graphite carbon nitride powder, methylhydrazine can be more easily transferred and aggregated in the catalyst. At the same time, the polymer semiconductor polyaniline promotes the transfer of holes and electrons generated by graphite carbon nitride under ultraviolet light to the surface of the material, thereby showing a better degradation effect.

[0151] The present invention is not limited to the above-mentioned embodiments. On the basis of the technical solution disclosed in the present invention, technicians in this field can make some substitutions and deformations to some technical features therein according to the disclosed technical content without creative labor, and these substitutions and deformations are all within the protection scope of the present invention.

Claims

1. A gC 3 N 4 Preparation method of hydrogel composite aniline hydrogel, It is characterized in that include: a. Melamine is heated in stages to obtain gC 3 N 4 Powder and gC 3 N 4 Nanosheets; b. Stir and mix N,N'-methylenebisacrylamide, alkali solution, initiator and aniline in a mass ratio of (5-10):1:(1-2):(1.5-2.5) in a water bath to obtain solution A; Heat solution A in a water bath until solidified, place the solidified product in deionized water to absorb water, obtain a hydrogel, and refrigerate for later use; c. Add concentrated sulfuric acid-aniline solution, gC 3 N 4 The nanosheets, phytic acid and hydrogel are stirred and mixed in a mass ratio of (2.0-4.0): (0.5-1.0): (0.5-1.0): 1, and allowed to stand, and then (0.03-0.05) ammonium persulfate is added to the mixed solution to obtain solution B; The hydrogel and mixed solution B were sealed at low temperature in an environment of 0-5 ℃ for 36-60 h to obtain a porous structure gC 3 N 4 Hydrogel composite aniline hydrogel.

2. gC according to claim 1 3 N 4 Preparation method of hydrogel composite aniline hydrogel, It is characterized in that In step a, melamine is heated to 450-600°C and maintained for 2-6 h at a heating rate of 1-10°C / min to obtain a yellow gC 3 N 4 powder; G C 3 N 4 The powder is heated to 450~600℃ and maintained for 2~6 h to obtain a light yellow gC 3 N 4 Nanosheets.

3. gC according to claim 1 3 N 4 Preparation method of hydrogel composite aniline hydrogel, It is characterized in that The alkali solution is sodium hydroxide, potassium hydroxide or ammonia water.

4. gC according to claim 1 3 N 4 Preparation method of hydrogel composite aniline hydrogel, It is characterized in that The initiator is potassium persulfate, sodium persulfate or ammonium persulfate.

5. gC according to claim 1 3 N 4 Preparation method of hydrogel composite aniline hydrogel, It is characterized in that The concentrated sulfuric acid-aniline solution is prepared according to a volume ratio of concentrated sulfuric acid to aniline of (20-30):

1.

6. gC according to claim 1 3 N 4 Preparation method of hydrogel composite aniline hydrogel, It is characterized in that In step b, solution A is poured into a rubber-tipped dropper and heated in a water bath at 50 to 70°C for 3 to 6 hours until completely solidified. The solidified material is taken out and absorbed in deionized water for 20 to 28 hours, and the deionized water is replaced every 5 to 8 hours. The hydrogel is refrigerated at -12 to -20°C for 10 to 15 hours, and thawed for 2 to 6 hours before being chopped.

7. gC according to claim 1 3 N 4 Preparation method of hydrogel composite aniline hydrogel, It is characterized in that In step c, the mixed solution is allowed to stand for 2 to 4 hours before adding ammonium persulfate to the mixed solution.

8. A gC prepared by the method according to any one of claims 1 to 7 3 N 4 Hydrogel composite aniline hydrogel.

9. A gC according to claim 8 3 N 4 Method for degrading methylhydrazine by using hydrogel composite aniline hydrogel, It is characterized in that include: Add 6-9 g / L gC in the wastewater containing methylhydrazine according to the mass ratio 3 N 4 The hydrogel was composited with aniline hydrogel and 0.7-1.0 g / L permonosulfate, and the degradation reaction was carried out at pH 6-8 under ultraviolet light irradiation.